Innovación educativa con TIC. Google docs, una herramienta para la construcción social del conocimiento en la FID (Educación y Tecnología, 2012)
Abstract:Innovation in education is a challenge for every single educator because it involves the analysis of their context in order to optimize the procedures that are intended to generate learning. Information and communication technologies can become an important contribution to the development of a high quality education in this century. Nevertheless, it is essential to bear in mind that ICTs are just tools and not the objective; therefore it is fundamental to learn how and why we integrate them in the teachinglearning process, and which will be the role of those who will be part of the process. Initial teaching training also faces the challenge of contributing to the construction of a better education. This is the why in the following article describes its characteristics by linking them to both previously indicated themes.